FAMILIAL MEDITERRANEAN FEVER ASSOCIATED WITH ANKYLOSING SPONDYLITIS: A CASE REPORT - Şenay Özdolap,; Selda Sarıkaya,; Erol Aktunç, (Archives of Rheumatology, 2006)
Familial Mediterranean fever (FMF) is an autosomal recessive disease of unknown origin. A less common manifestation of joint involvement in FMF is spondylartropathy, which is almost always HLA B27 negative. In these patients, along with sacroiliitis, inflammatory neck and back pain is also present producing minimal or no radiographic changes on plain films of lumbar and cervical spine. In this report, we presented a patient with FMF whom had been diagnosed to be ankylosing spondilitis (AS) in the light of some clinical and radiological findings. (Rheumatism 2006; 21: 31-3)